Manajemen Evaluasi Hasil Belajar Kognitif, Afektif, Psikomotorik: Tatap Muka dan Daring - Plenden, Di Ohanes R. C.; Heni, Ana Maria; Laksmi, Javid Nama Ayu; Dwikurnaningsih, Yari; Satyawati, Sophia Tri (Universitas Muria Kudus, 2021)
In education sphere, evaluation management is needed to manage steps that will be taken to overcome the problem or res that been found. The intention of this study is to evaluate educational tool which is LP (Lesson Plan). LP (Lesson Plan) is a learning tool that designed learning process. Lesson Plan requires three areas which are cognitive, affective, and psychomotor. The analysed lesson plan was offline lesson plan Eleventh grade Bahasa Indonesia and online lesson plan twelfth grade mathematic from Satya Wacana Christian Senior High School. Researcher evaluate lesson plan and give suggestion and solution so the evaluation management could be run.